Controlling Words - Schiffrin, André (Sens public, 2014)
In June 2005, André Schiffrin gave a lecture at the Paris Sorbonne University, during the Seminary of Sens Public run by Gérard Wormser and Paul Zawadski. Author and publisher, André Schiffrin describes the present tendency to concentration in the press, and to creation of monopolies, as well in the United States as in Europe. On the same topic, he published two books : L’édition sans éditeur (La Fabrique, 2001) and Le contrôle de la parole (La Fabrique, 2005).